2013
DOI: 10.1159/000351137
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the Size of an Intracardiac Thrombus during Dabigatran Therapy (110 mg b.i.d.) in an Acute Cardioembolic Stroke Patient

Abstract: We report a case of atrial fibrillation in a patient in whom a mobile thrombus in the left atrial appendage increased in size after low-dose dabigatran therapy. A 74-year-old man was admitted to our hospital because of sudden onset of right hemiplasia and dysarthria. On admission, his National Institutes of Health Stroke Scale score was three. Axial diffusion-weighted magnetic resonance images and magnetic resonance angiography images showed hyperintense signals in the left front-parietal cerebral cortex witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
1
Order By: Relevance
“…Although Dabi appears to be an effective alternative to warfarin in preventing stroke or systemic embolism without requiring PT–INR monitoring, the fact that 4% of patients receiving Dabi still had LA thrombus in our survey suggests that TEE is useful when performed before elective ECV of persistent AF. Thrombus may develop even under Dabi treatment in the presence of mechanical heart valves or rheumatic mitral stenosis [12,13], but a few cases of failure to prevent LA thrombus formation with the use of this agent have also been reported in patients with AF without such backgrounds [14–16]. Although it is hard to prove, we speculate that not only higher CHADS 2 scores, but also the insufficient Dabi dosage given to some of our patients might have led to inadequate anticoagulation and subsequent clot formation.…”
Section: Discussionmentioning
confidence: 77%
“…Although Dabi appears to be an effective alternative to warfarin in preventing stroke or systemic embolism without requiring PT–INR monitoring, the fact that 4% of patients receiving Dabi still had LA thrombus in our survey suggests that TEE is useful when performed before elective ECV of persistent AF. Thrombus may develop even under Dabi treatment in the presence of mechanical heart valves or rheumatic mitral stenosis [12,13], but a few cases of failure to prevent LA thrombus formation with the use of this agent have also been reported in patients with AF without such backgrounds [14–16]. Although it is hard to prove, we speculate that not only higher CHADS 2 scores, but also the insufficient Dabi dosage given to some of our patients might have led to inadequate anticoagulation and subsequent clot formation.…”
Section: Discussionmentioning
confidence: 77%
“…Vidal and Vanerio [4] reported a case, in whom 6 weeks of dabigatran therapy (300 mg/day) shrunk and resolved left atrial thrombus. We also previously reported that [5] low-dose dabigatran was not sufficient to reduce the size of a left atrial thrombus. In the case, a 6-week treatment with dabigatran (220 mg/day) increased the thrombus size from 10 mm  22 mm to 15 mm  30 mm.…”
Section: Discussionmentioning
confidence: 89%
“…Противоположные результаты показывает случай, описанный Tabata и соавт. [24]: у 74-летнего пациента с неклапанной ФП при ЧПЭхоКГ был обнаружен мобильный тромб (1,0×2,2 см) в ушке ЛП, и начата терапия дабигатраном (110 мг 2 р/сут). Повторная ЧПЭхоКГ через 1 нед выявила, что размеры тромба увеличились до 1,5×3,0 см.…”
Section: Discussionunclassified